2011
DOI: 10.1124/jpet.111.180711
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide in the Rostral Ventrolateral Medulla Inhibits Sympathetic Vasomotor Tone through ATP-Sensitive K+ Channels

Abstract: Hydrogen sulfide (H 2 S) acts as an endogenous gaseous transmitter in the central nervous system and plays important roles in regulating cardiovascular function. The rostral ventrolateral medulla (RVLM) is a putative critical central region in the control of sympathetic vasomotor tone and plays an important role in the baroreflex by integrating the inputs from a variety of visceral and somatic stimuli. In this study, we tested the hypothesis that H 2 S decreases sympathetic vasomotor tone through ATP-sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 33 publications
2
30
1
Order By: Relevance
“…One experiment has suggested that NaHS evokes a concentration-dependent hyperpolarization and decreases the input resistance of CA1 neurons by opening of K ATP channels (24). In addition, microinfusion of NaHS into the RVLM decreases arterial blood pressure by opening K ATP channel in rats (13). These results indicate that K ATP channels are involved in the action of H 2 S in the central nervous system.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…One experiment has suggested that NaHS evokes a concentration-dependent hyperpolarization and decreases the input resistance of CA1 neurons by opening of K ATP channels (24). In addition, microinfusion of NaHS into the RVLM decreases arterial blood pressure by opening K ATP channel in rats (13). These results indicate that K ATP channels are involved in the action of H 2 S in the central nervous system.…”
Section: Discussionmentioning
confidence: 62%
“…Previous experiments have demonstrated that bilateral microinjection of sodium hydrosulfide (NaHS), an H 2 S donor, into the RVLM decreases arterial blood pressure, and the CBS inhibitor hydroxylamine (HA) produces a pressor response (13). Contrary, another study has shown that the microinjection of NaHS into the RVLM has no effect on mean arterial pressure (MAP) (26).…”
mentioning
confidence: 80%
See 3 more Smart Citations